2013
DOI: 10.1097/mph.0b013e31827f0add
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler Ultrasonography in Sickle Cell Disease

Abstract: Changes on Transcranial Doppler (TCD) ultrasonography have been proposed as significant predictors of cerebrovascular complications in sickle cell disease (SCD). However, consensus with regards to the TCD criteria to recognize abnormalities in cerebral vasculature is lacking. We studied the TCD characteristics of cerebral arteries among Omani patients with SCD and correlated them with cerebrovascular events. TCD was performed through the temporal and suboccipital windows using a 2 MHz probe (DWL). Thirty-three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This finding was consistent with the reported figures of approximately 1.0% for childhood stroke among patients with SCD and the AI haplotype . A previous study, from Oman, which included adult patients, reported stroke prevalence of 20% among its patients but did not indicate how many had the AI haplotype …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding was consistent with the reported figures of approximately 1.0% for childhood stroke among patients with SCD and the AI haplotype . A previous study, from Oman, which included adult patients, reported stroke prevalence of 20% among its patients but did not indicate how many had the AI haplotype …”
Section: Discussionsupporting
confidence: 91%
“…Table shows reported transcranial Doppler values from the United States, France, Brazil, Tanzania, Nigeria, and Iran in which the proportions with abnormal values ranged from 1.6% to 20.7%. However, the 2 studies from the Arabian Peninsula (Oman and Kuwait) did not record any abnormal values, whereas the study from Iran reported 3% . The question therefore arises of whether the results from these countries could be reproduced among other Peninsular Arabs, and whether this variation is related to the β S haplotypes, HbF level, and hydroxyurea therapy or race/ethnicity.…”
Section: Classification Of Tammv Values Reported From Different Countmentioning
confidence: 96%
“…This suggests low progression of cerebral vasculopathy among these patients. Interestingly, however, this sparing of the cerebral vessels is not only limited to patients with the AI haplotype, as reports from Oman 17,18 , Iran 15 and Iraq 16,19 , where this haplotype is not particularly common, also report relatively normal TCDI indices. Therefore, there may be other obscure factors in this population that protect them from neurological events.…”
Section: Discussionmentioning
confidence: 77%
“…According to the frequency of blood transfusion, the right MCA (PSV), left DICA (PSV) & both DICA (TAmax) had a significant correlation with the frequency of blood transfusion, and this finding is in accordance with prior research. Abd-Allah et al [36] which showed that the annual frequency of blood transfusion and HU dose was associated with a decreased frequency of abnormal TCD findings, but is opposite to Bowman et al [37]; Gujjar et al [38] that had reported that The differences in Doppler velocities noted were not significantly different between patients who had been transfused within 3 months of examination, and those who had not received transfusions.…”
Section: Discussionmentioning
confidence: 87%